"Hidden stories behind global love": Acculturative and social integration challenges of marriage migrant women in South Korea. (July 2022) - Wijerathna, Mandari Pabasara; Hewapathirana, Gertrude I.
Abstract: This research explored the acculturative challenges and social integration issues faced by marriage migrant women in Korea. Using acculturation and integration theory lenses, the authors analyzed the lived experiences of marriage migrant women. Data were collected using open-ended probing interviews with 19 participants from Asian countries to capture their lived experiences. The emergent themes were clustered into two domains: acculturative challenges and difficulties in integrating encountered during post-migration. These themes portray the ongoing enigmas between pre-migration expectations versus post-migration realities. This study is a unique example of the Asian context, which captured hidden realities and present implications and future directions for many stakeholders. The findings of this research can be used as a reference to find solutions to acculturative and social integration issues of migrant women in similar contexts. The authors believe that the findings can be generalizable to other Asian countries.